Covalent 2D Cr2Te3 ferromagnet. Issue 5 (4th May 2021) - Bian, Mengying; Kamenskii, Aleksandr N.; Han, Mengjiao; Li, Wenjie; Wei, Sichen; Tian, Xuezeng; Eason, David B.; Sun, Fan; He, Keke; Hui, Haolei; Yao, Fei; Sabirianov, Renat; et al.
ABSTRACT: To broaden the scope of van der Waals 2D magnets, we report the synthesis and magnetism of covalent 2D magnetic Cr2 Te3 with a thickness down to one-unit-cell. The 2D Cr2 Te3 crystals exhibit robust ferromagnetism with a Curie temperature of 180 K, a large perpendicular anisotropy of 7 × 10 5  J m −3, and a high coercivity of ∼4.6 kG at 20 K. First principles calculations further show a transition from canted to collinear ferromagnetism, a transition from perpendicular to in-plane anisotropy, and emergent half-metallic behavior in atomically-thin Cr2 Te3, suggesting its potential application for injecting carriers with high spin polarization into spintronic devices. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: A TC of 180 K, a perpendicular anisotropy of 7 × 10 5  J m −3, and a high coercivity of ∼4.6 kG were achieved in covalent Cr2 Te3 2D ferromagnets.